Factors affecting nutritional attitudes among university adults - Jamal Abdul Nasir; M. H. Tahir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The problem of malnutrition has never been good and the information regarding nutrition would be advantageous particularly in case of Pakistan because significant progress of nutrition awareness at regional level is scarce. The focus of this study is to assess the nutritional believes, practice, awareness and participation of university adults towards nutrition. A cross-sectional data on 756 university students was taken. The multivariate regression models are used to find the most significant variables that influence the adult's attitudes of nutrition awareness. The results revealed that nearly 70 per cent of the adults have no regular meal routine per day. Three types of multivariate models (nutritional awareness, obesity index, meal trait) of nutritional attitudes are estimated. Across three models, males are about two times more obese than female adults. Meal trait has a strong effect on nutritional awareness. This study suggests that the significant factors that may affect nutrition attitudes are gender, district of campus, exposure of cardiovascular diseases, knowledge of diabetes, fat level awareness, obesity and meal trait. It is expected that this study would provide nutritional status of adults which is scarce at regional level in Pakistan.
Keywords: 330; obesity index; meal trait; nutrition; nutritional attitude; hazard ratio